KEHIDUPAN SOSIAL EKONOMI PETANI DAUN BAWANG DI DESA GUAAN KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Goni, Skivi Klara (HOLISTIK, Journal of Social and Culture, 2024)
Indonesia is an archipelagic country that has different geographical locations, for example differences in the height and low of a community's residence. The existence of different natural factors that are owned can affect different climates and weather which also result in different livelihoods in Indonesian people, such as farmers, fishermen, other plantation fields such as coffee, tea, tobacco, clove, plantations. Indonesian people who live in mountainous areas make a living in plantations, lowland areas pursue agriculture and those in coastal areas as fishermen. Farmers in Guaan Village are divided into two categories, namely as cultivators, namely farmers who work on other people's land and work in their own gardens, namely farmers who cultivate their own land. But Most farmers become cultivators in people's gardens. They plant leeks (Allium fistulosum L.) because in addition to the large enough yield, this plant also has a fast growth period so that farmers get money faster from this plant. Most farmers in Guaan Village choose to become Leek Farmers (Allium fistulosum L.) because the yield and profit are quite large and can meet their daily needs. Farmers are one of the sources of income and economy for humans, having fertile land and crops can make a person achieve daily needs and can also pay for the schooling of farmer children to college. Keywords: socioeconomic life, farmer, leek